Analisis Kasus-Kasus Pernikahan WNI di Luar Negeri dalam Konteks Hukum Perdata Internasional - Dwi Ariska, Meliana; Adi Saputra, Singgih; Faizal, Mochamad; Mul Erowati, Eti (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
ABSTRACT Marriage of Indonesian citizens (WNI) abroad is becoming an increasingly common phenomenon along with increasing global mobility. This research aims to explore the legal and social aspects of Indonesian citizen marriages abroad, with a focus on legal validity, registration, and the social impacts faced by Indonesian citizen couples. The background to this research shows that many Indonesian citizens marry foreign nationals (WNA) or fellow Indonesian citizens abroad, but they often face challenges in legal recognition of these marriages in Indonesia. This is important to understand considering that unrecognized marriages can have an impact on the legal status, inheritance rights and citizenship of children. The method used in this research is a qualitative approach with data collection techniques through in-depth interviews with Indonesian citizens who have married abroad, analysis of legal documents related to international marriage, as well as literature studies to understand the wider legal and social context. The research results show that the validity of an Indonesian citizen's marriage abroad is recognized if it meets the legal requirements of the country where the marriage takes place. However, marriage registration in Indonesia is often hampered by a lack of information and complicated procedures. Many Indonesian citizens also experience social stigma and difficulties in accessing legal rights, especially regarding children's citizenship and inheritance rights.